2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318984
|View full text |Cite
|
Sign up to set email alerts
|

Investigating deep learning for fNIRS based BCI

Abstract: Functional Near infrared Spectroscopy (fNIRS) is a relatively young modality for measuring brain activity which has recently shown promising results for building Brain Computer Interfaces (BCI). Due to its infancy, there are still no standard approaches for meaningful features and classifiers for single trial analysis of fNIRS. Most studies are limited to established classifiers from EEG-based BCIs and very simple features. The feasibility of more complex and powerful classification approaches like Deep Neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…More recently, initial studies have successfully applied deep learning methods to brain data [25,26,27] and BCI applications [28,29,30,31,32,33]. Here, we show that densely-connected convolutional neural networks can be trained on limited training data to map ECoG dynamics directly to a speech spectrogram.…”
Section: Introductionmentioning
confidence: 76%
“…More recently, initial studies have successfully applied deep learning methods to brain data [25,26,27] and BCI applications [28,29,30,31,32,33]. Here, we show that densely-connected convolutional neural networks can be trained on limited training data to map ECoG dynamics directly to a speech spectrogram.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, artificial intelligence methods based on deep learning have demonstrated their potential in enhancing the performance of BCI systems (Cecotti and Graser, 2011;Chiarelli et al, 2018;Lawhern et al, 2018;Nicholas et al, 2018;Sakhavi et al, 2018). Even though some studies have reported the superiority of the deep learning-based approach compared to the conventional machine learning methods (Trakoolwilaiwan et al, 2018), there still exist controversies regarding the employment of these opinions (Hennrich et al, 2015). Since deep learning techniques generally depend on human factors, such as how well the deep learning model structure is designed, objective and thorough investigations of deep learning models that can enhance the performance of NIRS-BCIs are necessary.…”
Section: Efforts To Improve the Performance Of Nirs-bcis: Future Persmentioning
confidence: 99%
“…However, it is useful to obtain the results in real-time to provide feedback to the clinicians. The deep learning method allows fast retrieval of parameters and been used recently in the diffuse optical field, including functional near-infrared spectroscopy [12][13][14], spatial frequency domain imaging [15], fluorescence imaging and tomography [16][17][18]. Its application for DCS has yet to be established [19].…”
Section: Introductionmentioning
confidence: 99%